An empirical analysis of the effects of humor on communication satisfaction and job performance in international joint ventures in Iran. (1st August 2016) - Jalalkamali, Mohammad; Iranmanesh, Mohammad; Nikbin, Davoud; Hyun, Sunghyup Sean
Abstract: This study investigates the relationships between humor (frequency and effectiveness), communication satisfaction (informational and relational), and employee job performance (task and contextual) in international joint ventures in Iran. Based on a survey of 375 employees and their supervisors in two of the biggest joint ventures in the automotive industry in Iran, the results indicate that the frequency of humor had significant positive effects on contextual and task performance as well as on informational and relational communication satisfaction. In addition, informational communication satisfaction was significantly related to both contextual performance and task performance, whereas relational communication satisfaction was related only to task performance. Finally, informational communication satisfaction mediated the relationship between the frequency of humor and job performance (task and contextual), while relational communication satisfaction mediated the relationship between the frequency of humor and task performance.